Human responses in adolescents with oncological disease: a scoping review protocol - Gonçalo Miguel Guerreiro; Sérgio Deodato; Daniela Graça; Catarina Fernandes (BMJ Open, 2023)
Introduction The classification of human responses to health conditions or life processes, assuming that human responses are the way that a person responds, referring to the individual’s experiences, feelings, perceptions, behaviours and physical reactions, can be an exercise that, although challenging, is central to nursing diagnoses and, consequently, to nursing practice. It is necessary to gather and organise the existing knowledge about the human responses in adolescents with cancer, starting from the moment of diagnosis, due to the specificities inherent to this stage of human development. A scoping review is an appropriate method to use in order to map the existing knowledge on human responses in adolescents with oncological diseases experienced since the diagnosis.Inclusion criteria Will encompass all types of studies, including ‘grey literature’ that centres on human responses related to adolescents aged 10–19 years with oncological diseases. There will be no restrictions based on the type of cancer, disease stage or other contextual factors, whether in home or healthcare settings.Methods and analysis The review will be conducted following the guidelines outlined by the Joanna Briggs Institute for scoping reviews. The search will encompass the following databases: CINAHL Complete (EBSCOhost), Cochrane Database of Systematic Reviews (EBSCOhost), MEDLINE Complete (EBSCOhost), Nursing and Allied Health Collection: Comprehensive (EBSCOhost), Cochrane Clinical Answers (EBSCOhost Answers), Latin American and Caribbean Literature on Health Sciences (LILACS) and ‘grey literature’ sources accessible through the Scientific Open Access Repositories of Portugal (RCAAP). A three-step search strategy will be implemented. Titles and abstracts will undergo analysis by two independent reviewers. Articles selected for a full-text review will be organised. The results will be presented in tables and narratively summarised.Ethics and dissemination Ethics approval and patient consent for publication are not necessary. Findings will be disseminated through publication in scientific journals and through conference presentations.Review registration number EXUB4. Registration was made in the Open Science Framework (OSF).